Pengaruh Motivasi Terhadap Minat Mahasiswa Akuntansi Untuk Mengikuti Pendidikan Profesi Akuntansi (PPAk) (Studi Pada Mahasiswa Prodi Akuntansi STIE Al-Anwar Mojokerto) - Lely Fithri Nela Margarita; Hari Setiono; Tatas Ridho Nugroho (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2019)
The accounting profession education is an additional education that must be followed by accounting graduates, the minimum number of public accountants today is one that is faced by the public accounting profession who want to get an accountant degree, this study aims to provide evidence of the influence of motivation on the interest of STIE Al-Anwar accounting students to take up the accounting profession education (PPAk). This type of research uses a quantitative approach. The population of this study were 456 students in semester 2 to 8. The sample was determined using 2 purposive sampling and simple random sampling methods, and obtained a total sample of research as much as 50 samples. Data collection techniques using questionnaires. This study uses a Likert Scale as a questionnaire score. Data analysis used is descriptive analysis, while the analysis used in this study is multiple linear regression analysis. The results of the study prove that partially the quality motivation and economic motivation variables have a significant effect on students 'interest in participating in PPAk while career motivation variables do not affect students' interest to participate in PPAk. Simultaneously quality motivation, career motivation and economic motivation affect student interest in participating in PPAk. Determination coefficient results is 0.255 which means that the ability of the independent variable can explain the dependent variable by 25.5% while the remaining 74.5% is explained by other variables, which are not included and are not included in the regression model used.